1975
DOI: 10.1038/bjc.1975.254
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture studies of malignant effusions

Abstract: Summary.-This study reports attempts to culture tumour cells from 51 malignant effusions using standard tissue culture techniques. Cultures proliferating for more than one month were derived from 42 effusions including 24/32 from breast cancer patients and 5/6 from colon carcinomata. The morphology of these cells and their culture characteristics were compared with that of cells derived from a benign effusion. A common cell type-believed to be of mesothelial origin-was found in all cultures. In addition, fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…Cultures in which TC either failed to grow or were initially absent were used as a source of MC. Characterisation involved recognition of the following criteria, some of which have been described in the literature (Mouriquand et al, 1978;Whitehead & Hughes, 1975) (Wilson et al, 1987), although there are varied reports in the literature which describe positive staining of some benign MC in wax-embedded tissue (Ghosh et al, 1987) and negative staining in wet-fixed smears (Epenetos et al, 1982). MC used in this study stained positively for both vimentin and keratin, as has been previously reported (Connell & Rheinwald, 1983) whereas epithelial cells were, until recently, believed to express only keratin.…”
Section: Tumour Cellsmentioning
confidence: 99%
“…Cultures in which TC either failed to grow or were initially absent were used as a source of MC. Characterisation involved recognition of the following criteria, some of which have been described in the literature (Mouriquand et al, 1978;Whitehead & Hughes, 1975) (Wilson et al, 1987), although there are varied reports in the literature which describe positive staining of some benign MC in wax-embedded tissue (Ghosh et al, 1987) and negative staining in wet-fixed smears (Epenetos et al, 1982). MC used in this study stained positively for both vimentin and keratin, as has been previously reported (Connell & Rheinwald, 1983) whereas epithelial cells were, until recently, believed to express only keratin.…”
Section: Tumour Cellsmentioning
confidence: 99%
“…The establishment and general properties of melanoma cell lines MM 96, MM 127, MM 138 and MM 170 have been described elsewhere (Whitehead and Little, 1973). Lines MM 200 and MM 214 were established from a pedunculated primary tumour and a lymph-node secondary tumour respectively.…”
Section: Biological Materialsmentioning
confidence: 99%
“…It is interesting in this context that Cailleau et al (1975) have described the growth of breast cancer cells from pleural effusions using Leibowitz L15 medium which is very hypertonic (369 mosm/kg). These conditions may have selected for the tumour cells rather than the mesothelial cells which are also present in these effusions and which grow extremely well under normal conditions (Whitehead and Hughes, 1975). It is evident from these findings that the osmolalities of the commonly used tissue culture media still vary as widely as when Waymouth reviewed the subject in 1970.…”
Section: Implications Of the Osmolalities Of Some Commonlymentioning
confidence: 98%